Ventilatory thresholds in professional female soccer players - Parpa, K.; Michaelides, M. A. (International Journal of Sports Medicine, 2025)
This study investigated the ventilatory thresholds (VT1 and VT2) along with the corresponding heart rates, velocities and % of VO2 max at which these thresholds are reached in professional female soccer players. It also examined positional differences in the aforementioned parameters. Thirty-three professional players from two teams (age range 18-31 years) were recruited. The players underwent maximal exercise testing on the treadmill for the detection of VT1 (VE versus VO2 plot) and VT2 (VE versus V?CO2 plot). The test began at a speed of 6km/h and was increased by 2 km/h every 3.15 minutes, with the inclination constant at 1%. Results indicated that the players had an average VO2 max of 50.24 ml·kg- 1.min- 1. VT1 (% max) and VT2 (% max) were shown at 72.87% and 91.26% of VO2 max, respectively. The respective velocities at VT1 and VT2 were indicated at 10.85 km/h and 12.91 km/h, respectively, while the average VVO2 max was 14.61 km/h. The average heart rates at VT1, VT2 and VO2 max were 159.33, 185.15 and 192.85 beats per minute, respectively. Furthermore, analysis of variance ANOVA indicated significant differences in velocity at VO2max. This study provides important normative data regarding the ventilatory thresholds of female soccer players.